Analysis of Marketing Strategy in the Home Sewing Business "Mbak Jar" - Febriyan, Rahmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to describe the application of marketing strategies in the home sewing business "Mbak Jar" and to identify the obstacles faced in the marketing strategies of this business. This type of research uses qualitative research with a case study design. The validity of the data is carried out through qualitative triangulation of sources and methods. Data collection techniques used are interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions and verification. The results of the study show that this sewing business targets a specific market segment, namely individuals who need clothing repair and tailoring services, focusing on housewives, students, office workers, TNI members, and police officers. The marketing mix of this business includes high-quality products with personal designs, competitive prices, strategic location, and promotion through word-of-mouth marketing and WhatsApp. SWOT analysis shows that the main strength lies in the quality of stitching and service, while weaknesses include limitations in social media promotion. The main obstacle faced is in digital marketing, with the strategies applied still limited and lacking mastery of social media technology, affecting the business's ability to maximize its online promotion potential. The SWOT analysis indicates that this sewing business faces tight market competition, changing consumer preferences, and unstable economic conditions, which can affect customers' purchasing power and the need for services.